Transcriptomic and Targeted Metabolomics Analysis of Detached Lycium ruthenicum Leaves Reveals Mechanisms of Anthocyanin Biosynthesis Induction through Light Quality and Sucrose Treatments - Haitao Zeng; Tao Zheng; Xue Peng; Qi Tang; Hao Xu; Mengjiao Chen (Metabolites, 2023)
Light quality and sucrose-induced osmotic stress are known to cause anthocyanin synthesis in detached Lycium ruthenicum leaves. To identify the mechanisms by which the kind of light quality and sucrose concentration are induced, here, we conducted transcriptome sequencing in detached L. ruthenicum leaves treated with different qualities of light and sucrose concentrations. Leaves treated with blue light or sucrose showed a significantly increased total anthocyanins content compared to those treated with white light. Delphinidin-3-O-rutinoside and delphinidin-3-O-glucoside production were differentially regulated by the BL(−S), BL(+S), and WL(+S) treatments. The structural genes CHS, CHI, F3′H, F3′5′H, ANS, and UFGT were significantly up-regulated in leaves treated with blue light or sucrose. Leaves treated with blue light additionally showed up-regulation of the light photoreceptors CRY1, PIF3, COP1, and HY5. The anthocyanin-related genes NCED1, PYR/PYL, PP2C, SnRK2, and ABI5 were significantly up-regulated in leaves treated with sucrose, promoting adaptability to sucrose osmotic stress. Co-expression and cis-regulatory analyses suggested that HY5 and ABI5 could regulate LrMYB44 and LrMYB48 through binding to the G-box element and ABRE element, respectively, inducing anthocyanin synthesis in response to blue light or sucrose treatment. Candidate genes responsive to blue light or sucrose osmotic stress in the anthocyanin biosynthesis pathway were validated through quantitative reverse transcription PCR. These findings deepen our understanding of the mechanisms by which blue light and sucrose-induced osmotic stress regulate anthocyanin synthesis, providing valuable target genes for the future improvement in anthocyanin production in L. ruthenicum.